Veil: veiling, representation, and contemporary art - Tawadros, Gilane; Bailey, David A. (MIT Press ; IVA, 2003)
No single item of clothing has had greater influence on Western images of Middle Eastern and North African women than the veil. The fascination of Western writers, artists, and photographers with the veil reflects the voyeuristic nature of our interest in what is strange and "other." Veil, which accompanies an exhibition organized by the Institute of International Visual Arts in London, explores the representation of the veil in contemporary visual arts. Providing a context for the commissioned essays are a number of classical historical texts crossing religions, cultures, genders, and ages--from Greek myths to articles published in the aftermath of September 11, 2001. Some of the contemporary artists and scholars write autobiographically about the meaning of the veil in their lives. Others take a more political approach, discussing, for example, how the events of September 11 changed the use and reception of veil imagery throughout the world. Still others take a historical approach, examining how nineteenth-century technological developments in travel and photography led to photographic depictions of both the veiled and unveiled body in relation to landscape. A number of essays look at the art historical precedents for the current interest in artwork addressing the veil, while others examine how codes of modesty and gender segregation have affected the making and viewing of films in postrevolutionary Iran. The essays are by Jananne Al-Ani, David A. Bailey, Alison Donnell, Ghazel, Salah Hassan, Reina Lewis, Hamid Naficy, Zineb Sedira, and Gilane Tawadros. The artists represented include Faisal Abdu'Allah, Kourosh Adim, Ghada Amer, Jananne Al-Ani, Farah Bajull, Samta Benyahia, Gaëtan de Clérambault, Marc Garanger, Shadafarin Ghadirian, Group AES, Emily Jacir, Ramesh Kalkur, Shirin Neshat, Harold Offeh, Gillo Pontecorvo, Zineb Sedira, Mitra Tabrizian, and Elin Strand.
Keywords: afrique; afrique du nord; approches et analyses; arts; corps; cours; discipline; féminisme islamique; har4610; histoire de l'art; mode; moyen-orient; point de vue situé; premier cycle; régions géographiques; thématiques; vêtements

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques